2021
DOI: 10.5070/t5131047083
|View full text |Cite
|
Sign up to set email alerts
|

Learning Design and Student Behavior in a Fully Online Course

Abstract: Student's behavior in an online course is strongly influenced by the learning design of the course, however there are not many discipline-focused studies investigating how students engage with the Learning Management System and course materials. This paper investigates an asynchronous and fully online introductory statistics course with a collaboration component (Collaborative Keys). This study evaluates how students use these and other resources, if they are being used as intended, and how the use is related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Finally, overall access to CKs was less varied for A or B students throughout the quarter, but many C and D or F students seemed to give up on accessing this resource after the first midterm. Similarly, Sabbag and Frame (2021) also reported that the average number of clicks per student on the CKs typically decreased throughout the term but specifically after the first midterm.…”
Section: Data Analysis and Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…Finally, overall access to CKs was less varied for A or B students throughout the quarter, but many C and D or F students seemed to give up on accessing this resource after the first midterm. Similarly, Sabbag and Frame (2021) also reported that the average number of clicks per student on the CKs typically decreased throughout the term but specifically after the first midterm.…”
Section: Data Analysis and Resultsmentioning
confidence: 80%
“…Of course, it is encouraging for the instructor to know that students seem to prefer to access instructor-created videos than textbook resources; however, access to videos does not necessarily mean that students were actually watching them. Moreover, the access was not constant throughout the course for the majority of students (see Sabbag & Frame, 2021).…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many ways to integrate this idea in undergraduate statistics curriculum. As one example, statistics instructors can involve their students in the process of generating course material by co-creating the course structure with students or asking students to make collaborative answer keys for homework assignments (Sabbag & Frame, 2021). As another idea, statistics educators can also design course projects around emerging issues that directly impact their life or the society; guide students to use statistics as a powerful tool to gather useful information and identify potential problems behind those issues; quantify statistical evidence; and then encourage students to use that empirical evidence to come up with some actionable solutions, big or small, for the problems they identified.…”
Section: Engaging Students As Co-creators and Partners Of The Coursementioning
confidence: 99%